A novel Ti(OH)4/graphene flame retardant towards reducing fire hazards of phenolic resin. (December 2022) - Zhi, Maoyong; Yang, Xiong; Xin, Hui; Li, Yuchuan; Fan, Rong; Zhao, Yinlong; Liu, Quanyi; He, Yuanhua
Abstract: Ti(OH)4 /graphene was synthesized by hydrolysis of titanium tetrachloride into titanium hydroxide and precipitation on the surface of graphene nanosheets, and was incorporated into phenolic resin to prepare phenolic composites using hexamethylenetetramine as a curing agent. After that, the effects of Ti(OH)4 /graphene on the thermal stability, flame retardancy, and smoke suppression properties of phenolic matrix were studied. When the content of Ti(OH)4 /graphene was 5 wt%, phenolic composites passed the UL‐94 V‐0 rating with a limiting oxygen index (LOI) of 28.6%, and the residual char at 800 °C was 56.83 wt%. Cone calorimeter tests demonstrated that the peak heat release rate (pHRR), total heat release (THR) and total smoke production (TSP) of phenolic composite contained 10 wt% Ti(OH)4 /graphene were 86.3 kW/m 2, 30.74 MJ/m 2 and 1.8 m 2, respectively, which were reduced by 41.85%, 24.82%, and 30.78% compared with pure phenolic resin. And the smoke density test also showed that the smoke density of phenolic composite contained 10 wt% Ti(OH)4 /graphene had a 51.89% reduction. These data indicated that Ti(OH)4 /graphene can effectively improve the flame retardant and smoke suppression performance. Moreover, the char residue after combustion is investigated using SEM, FTIR, XRD and Raman technologies, and the results demonstrated that Ti(OH)4 /graphene could greatly promote the formation of a continuous and dense char residue layer in phenolic composites. Py-GC/MS results further revealed that the degradation products contents of phenolic resins were decreased by incorporating Ti(OH)4 /graphene. Therefore, the flame retardancy of phenolic composite is significantly improved through the mechanism of endothermic effect, coverage effect, and dilution effect of combustible gas. This feasible method can provide new insights for reducing fire hazards of phenolic resin. Graphical Abstract: ga1 Highlights: Ti(OH)4 /graphene was prepared and incorporated into phenolic resin as an additive flame retardant. Phenolic composites containing only 5 wt% Ti(OH)4 /graphene passed UL-94V-0 rating. Ti(OH)4 /graphene significantly improved flame retardancy performances of phenolic composites. The flame retardant mechanism of Ti(OH)4 /graphene in phenolic composites was investigated.